Bridge Engineering: Design, Rehabilitation, and Maintenance of Modern Highway Bridges, Fourth Edition - Zhao, Jim J.; Tonias, Demetrios E. (McGraw-Hill Education, 2017)
Bridge engineering essentials-fully updated to reflect the latest standards and regulations.